Manfaat Majelis Ta’lim Jammassan Di Masyarakat Ngadiluwih Kediri - Iqlima Zahari (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The term majelis ta’lim derived from Arabic, has the meaning of a place of learning and teaching. The majelis ta’lim is non-formal educational institutions that is conducted regularly, periodically, has their own curriculum, followed by pilgrims, has the aim of fostering good relations between people, good relations with God, and good relations with the environment. Judging from the organizational structure, the majelis ta’lim include non-formal education (non-formal) which has special characteristics in Islamic studies. This research is a case study research, which was conducted at the Jammassan Ngadiluwih Assembly. This research was conducted to determine the activities and benefits of the majelis ta’lim. As for the activities of the Jammassan majelis ta’lim, among others: book study every Thursday night, fostering youth organizations, social services, fostering arts (banjary, habsy, hadrah, decoration), bahtsul masail, pilgrimage pilgrimage, the practice of scavenging bodies and so forth. The benefits of the Jammassan ta'lim assembly are divided into two categories. First, the benefits for the board, including training the board to play a role in the community, if needed. Second, the benefits for the community include: as a vehicle for sillaturrahmi, a place of learning, a vehicle for enlightenment, a spiritual recreation park for the community.